Perbandingan Implementasi dan Efektivitas Kebijakan Penanggulangan Pengangguran antara Pemerintah Kota Banda Aceh dan Kota Lhokseumawe - Natasya Bethari; Siti Rahima; Annisa Fatia Rizki; Nurul Kamaly; Reza Fahlevi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Unemployment remains a serious challenge in Aceh, with an Open Unemployment Rate (OUR) of 8.24% (2025) in Lhokseumawe City and 6.54% (2025) in Banda Aceh City. This study compares the implementation and effectiveness of unemployment alleviation policies in the two cities using Van Meter and Van Horn's policy implementation framework with four effectiveness indicators: training absorption, job placement rate, corporate compliance, and community participation. A descriptive qualitative method with a literature study approach was employed, utilizing secondary data from journals, theses, and official documents. The findings show that Banda Aceh focuses on competency-based training through the Job Training Center (BLK) with certification and third-party partnerships. Lhokseumawe prioritizes Qanun Number 1 of 2020 on local labor priority (minimum 40%). Based on the indicators, Banda Aceh is more effective (55% of graduates employed) compared to Lhokseumawe, where local labor priority implementation is weak due to the absence of sanctions and non-existent coordination with PT. PAG. The novelty of this study lies in its systematic comparison of two Acehnese cities using a policy implementation model that integrates demographic bonus and local context. Specific recommendations: Banda Aceh needs to expand BLK capacity, extend training duration (9–12 months with internships), and mandate graduate absorption reports. Lhokseumawe needs to revise the qanun by adding administrative sanctions, recruit permanent instructors, establish a tripartite supervisory team, and establish an energy-sector BLK in the Arun area in collaboration with PT PAG.